Principles of compilers a new approach to compilers including the algebraic method - Su, Yunlin; Yan, Song Y.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
Principles of Compilers: A New Approach to Compilers Including the Algebraic Method introduces the ideas of the compilation from the natural intelligence of human beings by comparing similarities and differences between the compilations of natural languages and programming languages. The notation is created to list the source language, target languages, and compiler language, vividly illustrating the multilevel procedure of the compilation in the process. The book thoroughly explains the LL(1) and LR(1) parsing methods to help readers to understand the how and why. It not only covers established methods used in the development of compilers, but also introduces an increasingly important alternative the algebraic formal method. This book is intended for undergraduates, graduates and researchers in computer science.
Introduction -- Grammars and Languages -- Finite State Automata and Regular Expressions -- Lexical Analysis -- Pushdown Automata -- Context-free Grammars -- Syntax Analysis -- Attribute Grammars and Their Analysis -- Algebraic Method for Compiler Design -- Generation of Intermediate Code -- Debugging and Optimization -- Storage Management -- Generation of Object Code -- Compilation of Object-Oriented Languages -- Compilation of Parallel Languages -- Compilation of Grid Computing.
Electronic reproduction.
Keywords: Compilers (Computer programs).; Electronic books